2018
DOI: 10.1007/s11356-018-2073-4
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of the adsorption of glyphosate and its degradation products on montmorillonite

Abstract: The most worldwide used herbicide is glyphosate, phosphonomethylglycine (PMG). Consequently, a significant amount of PMG, its metabolites (sarcosine, SAR, and aminomethylphosphonic acid, AMPA) and the degradation product, methylphosphonic acid (MPA), reaches the soil, which acts as final sink. Because clays are one of the most reactive components of soils, expansive clays such as montmorillonite (Mt) are used to retain agriculture contaminants with some success. In this work, as a preliminary step for the eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Carneiro et al (2011) found a pH pzc value of 1.42 for unmodified montmorillonite. Flores et al (2018) and Khoury et al (2010) also found a similar result for natural montmorillonite pH pzc (2.7).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Carneiro et al (2011) found a pH pzc value of 1.42 for unmodified montmorillonite. Flores et al (2018) and Khoury et al (2010) also found a similar result for natural montmorillonite pH pzc (2.7).…”
Section: Resultssupporting
confidence: 69%
“…3). Because interlayers of montmorillonite are negatively charged, glyphosate enters more easily in the montmorillonite interlayers when its concentration is high and its molecule is positively charged (Khoury et al, 2010;Ren et al, 2014;Flores et al, 2018). Thus, in the present work we can affirm that sorption process of glyphosate onto montmorillonite was through adsorption, meaning glyphosate adsorbed onto the surface of the mineral.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The adsorption of potentially toxic metals [7][8][9][10], herbicides [11][12][13][14][15] and dyes [16][17][18] has often been found in literature, since clay minerals consist of a low cost and high availability raw material, especially if compared to the usual adsorbent. Currently, some studies have focused on the adsorption of drugs present in water sources [19][20][21][22][23][24][25][26][27][28][29], Brazilian Journal of Development, Curitiba, v.7, n.1, p.5203-5222 jan. 2021 due to the harmful effects on flora, fauna and, consequently, on population.…”
Section: Introductionmentioning
confidence: 99%